Impact of macroeconomics variables toward Kuala Lumpur composite index (KLCI) - Chong, Min Khiuk (Universiti Malaysia Sarawak (UNIMAS), 2013)
This paper is attempted to investigate and evaluate the impact of macroeconomic variables toward Kuala Lumpur Composite Index, KL<;I. There are several variables that included in this study, namely consumer price index (CPI), money supply (MS), Malaysian Treasury bill (TBR), industrial production index (lPI), gold price (GP), oil price (OP). The data that obtained will tested by the Unit root test in order to ensure the stationary of the data All of the series data are significance after first difference was made, following by the Johansen co integration test to examine the long run relationship of the variables. It proved that, there exist long run and strong significance relationship be~ween Kuala Lumpur Composite Index and the selected variables. The study proceeds to Granger causality test revealed that there exist short run relationship between the Kuala Lumpur Composite Index and the variables namely consumer price index, money supply, Malaysia Treasury bill, industrial production index, gold price and oil price. After implemented these three tests, the result showed that the selected variables do have impact on the stock market in Malaysia. This study is important for those market participants and especially policy maker to understand behavior of the stock market as well in order to make right decision when doing their investment portfolio.